Review of engagement activities to promote awareness of radiation and its associated risk amongst the Japanese public before and after the Fukushima Daiichi Nuclear Power Plant accident. (24th November 2021) - Sakoda, Akihiro; Nomura, Naoki; Kuroda, Yujiro; Kono, Takahiko; Naito, Wataru; Yoshida, Hiroko
Abstract: Following the Fukushima Daiichi Nuclear Power Plant accident in 2011, many radiation experts directly experienced a vast gap between ideal and real public understanding (PU) of radiation in risk communication. Therefore, this study collated and reviewed information about PU activities for radiation and its risk that six Japanese academic societies—which seem to be socially neutral expert communities—related to radiation and radiation risk conducted before and after the accident. Activities these radiation-related societies provided to the general public were discussed from the following perspectives: (a) difficulties in two-way communication due to resources, motivation and public interest and concerns; (b) balance between academic research and PU activities; (c) academic societies' building trust with the public while ensuring member experts' neutrality and independence; and (d) discussions among academic societies to prepare for public engagement. We hope that this paper encourages experts and academic societies in radiation protection to hold more national and international discussions about their roles in public communication and outreach.